Efficacy and Safety of Direct Oral Anticoagulants in Elderly Patients With Atrial Fibrillation: A Network Meta-Analysis - Deng, Kaisheng; Cheng, Jinqun; Rao, Shufang; Xu, Huafu; Li, Lixia; Gao, Yanhui (Frontiers in Medicine, 2020)
Background: Direct oral anticoagulants (DOACs) have been widely used in patients with atrial fibrillation (AF) for antithrombotic prophylaxis, which were shown to have a favorable risk–benefit profile. However, there are no guidelines for the use of DOACs in elderly patients (aged ≥75 years) with AF, which creates uncertainty about the optimal antithrombotic treatment in these patients. Methods: After comprehensively searching Embase, PubMed, and Cochrane databases, five phase III randomized controlled trials involving 28,137 elderly participants were included in this study. The efficacy outcome was stroke or systemic embolism, and the safety outcome was major bleeding. We conducted a network meta-analysis by using a Bayesian random-effect model for the first time to evaluate the efficacy and safety of main DOACs (apixaban, edoxaban, rivaroxaban, and dabigatran) and warfarin in elderly patients with AF. Hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were used to assess the effect of drugs on efficacy and safety. The rank probabilities were used to reflect the hierarchy of drugs, and a larger rank probability value symbolized a better rank of drugs. Results: In the prophylaxis of stroke or systemic embolism, apixaban was found to be the best among DOACs compared to warfarin (HR, 0.71; 95% CI: 0.33–1.50), though this finding was not statistically significant. Apixaban ranked the best (rank probabilities, 41.2%) in efficacy of drugs, followed by rivaroxaban, edoxaban, dabigatran, and warfarin (rank probabilities, 31.8, 15.9, 10.9, and 0.2%, respectively). In reducing the risk of major bleeding, apixaban was found to be the best among DOACs too, compared to warfarin (HR, 0.64; 95% CI: 0.33–1.30), though this finding was not statistically significant. In safety, apixaban ranked the best (rank probabilities, 71.4%), followed by edoxaban, dabigatran, warfarin, and rivaroxaban (rank probabilities, 21.0, 5.8, 0.9, and 0.8%, respectively). Conclusions: DOACs showed a lower incidence of stroke/systemic embolism and major bleeding compared with warfarin in antithrombotic therapy in elderly patients (aged ≥75 years), with apixaban being the best of those interventions. Therefore, apixaban should be given priority as an anticoagulant in stroke prevention for elderly patients with AF.